Cultural beliefs and practices on perinatal death: a qualitative study among the Lango community in Northern Uganda - Anna Agnes Ojok Arach; Noeline Nakasujja; Joseph Rujumba; David Mukunya; Beatrice Odongkara; Milton W. Musaba; Agnes Napyo; James K. Tumwine; Victoria Nankabirwa; Grace Ndeezi; Juliet Kiguli (BMC, 2023)
Abstract Background Perinatal death has profound psychosocial effects on women and their families. Sociocultural contexts influence the burden, rituals and bereaved's support. Little is known about cultural beliefs and practices related to perinatal death. This study explored the cultural perspectives of the Lango community on perinatal death. Methods This study utilised a focused ethnographic design anchored on a symbolic interactionist framework to understand the meanings attached to beliefs and practices on stillbirth or neonatal death among the Lango community in Lira District, Northern Uganda. Participants were sampled purposively for FGD while key informants were identified through snowballing technique. Data were audio recorded in Lango, transcribed, and later translated, a codebook was developed and data entered into Atlas. ti version 8.4.26 and then coded. It was analysed both deductively and inductively into themes. Results Stillbirth and early neonatal death both attract similar rituals as would an older child. Burial is not rushed and is attended by family members and close friends. Stillbirths and children that die before naming are buried without names. Bereaved families are comforted and encouraged about future pregnancies. Currently, Lango associates the deaths to biomedical explanations such as teenage pregnancies, inadequate pregnancy care, health system challenges and poor health-seeking behaviour, unlike previously when they were attributed to consequences of unacceptable social behaviours, superstitious beliefs and witchcraft. Antenatal care and health facility childbirths are currently preferred over traditional practices for good pregnancy outcomes. Conclusion Stillbirth or early neonatal death is viewed as the death of a child, different from other settings. Thus, rituals are performed to honour, create memory, and maintain the connection with deceased babies. Bereaved parents are supported. Health care workers need to provide culturally sensitive support to parents after perinatal loss. The prevailing beliefs of perinatal death cause in terms of biomedical explanations consistent with known determinants and preference for health facility care for prevention creates an opportunity for improving perinatal health.